Bariatric surgery in the elderly: A narrative review - Cazzo,Everton (2017)
Summary Introduction: Due to population ageing, the elderly obese population is increasing. Bariatric surgery is the standard treatment option for morbid obesity nowadays, but there is some controversy regarding its routine indication in the elderly population. Objetive: To review the current evidence about bariatric surgery in the elderly. Method: On-line search in the electronic databases Medline and Lilacs and compilation of the most significant data. The most relevant studies in the area over the past 16 years have been considered for this review. Results: There was significant methodological heterogeneity in the studies found in the literature. Historically, old age was associated with poorer outcomes after bariatric surgery, both in regards to early postoperative complications and less weight loss, and resolution of comorbidities. More recent studies have shown better results, with morbidity and mortality comparable to those observed in younger populations. More cautious patient selection and the evolution of the surgical technique appear to be the cause of such improvement. An extended multidisciplinary team including a geriatrician and a social worker may also help to improve the preoperative approach. Conclusion: Bariatric surgery is a safe and effective therapeutic option in the elderly population, but careful patient selection and specific preoperative assessment are mandatory.